2011
DOI: 10.1523/jneurosci.6023-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Synapse Dynamics: Coordinated Presynaptic and Postsynaptic Mobility and the Major Contribution of Recycled Vesicles to New Synapse Formation

Abstract: Dynamics of GABAergic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
93
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 60 publications
10
93
0
Order By: Relevance
“…However, the ability of synapses to undergo synaptic plasticity (48,49) and the local coordination of these rearrangements (50) indicate that α-Nrxn-mediated functions should be locally modulated. Here, we propose that the α-Nrxn-specific binding partner Nxph1 subserves such a modulatory role in subpopulations of synapses.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability of synapses to undergo synaptic plasticity (48,49) and the local coordination of these rearrangements (50) indicate that α-Nrxn-mediated functions should be locally modulated. Here, we propose that the α-Nrxn-specific binding partner Nxph1 subserves such a modulatory role in subpopulations of synapses.…”
Section: Discussionmentioning
confidence: 99%
“…Images were analyzed in ImageJ (rsb.info.nih.gov/ij) using a custom plugin (rsb.info.nih.gov/ij/plugins/time-series.html). Rabbit vGAT-Oyster 550 luminal domain antibody was used to identify GABAergic neurons (23). Values are shown as mean ± SEM.…”
Section: Methodsmentioning
confidence: 99%
“…If isoflurane inhibits exocytosis purely by inhibiting AP-driven Ca 2+ entry, then the same quantitative relationship should hold. The paired isoflurane data fell on the control curve, which indicates that the effect of isoflurane on SV exocytosis can be attributed to reductions in [Ca 2+ ] i without significant contributing effects To compare the effects of isoflurane on SV exocytosis from glutamatergic or GABAergic neurons separately, we used livecell imaging of GABAergic boutons identified by vGAT-Oyster 550 immunolabeling (23) (Fig. 6A).…”
Section: Significancementioning
confidence: 99%
“…Gephyrin forms multimeric complexes that allow the anchoring of GABA A Rs (6) via molecular mechanisms that include phosphorylation and interactions with the guanine-nucleotide exchange factor collybistin (7)(8)(9)(10)(11)(12). In addition to changes in inhibitory strength, more recent in vivo experiments revealed that inhibitory synapses are also dynamic structures that can be formed and eliminated in response to sensory experience (13)(14)(15). The mechanisms implicated in the coordinated regulation of excitatory and inhibitory plasticity remain, however, poorly understood.…”
mentioning
confidence: 99%